Linking genetic variability to fruit and pyrene traits in Endopleura uchi genotypes from the Eastern Brazilian Amazon - R. J. C. Costa; J. I. M. Rodrigues; R. Gallo; T. R. Corrêa; S. H. S. Felipe; W. B. R. Martins (Brazilian Journal of Biology)
Abstract Endopleura uchi is a valuable tree species with significant nutraceutical potential and extensive applications. However, there is a lack of information regarding genetic parameters and the characterization of phenotypic variability that could be applied to the conservation and genetic improvement of this species. In this study, we estimated genetic parameters and quantified genetic variability based on the physical characteristics of fruits and pyrenes of E. uchi genotypes from a native population in the Eastern Brazilian Amazon. We collected 1,636 mature fruits from 13 genotypes and characterized them in terms of biometric measurements, volume, and fresh mass of both fruits and pyrenes. Additionally, we quantified the pulp yield from the fruit. Genetic analyses were conducted using the SELEGEN REML/BLUP software, model 81, and clustering analysis was performed using the unweighted pair group method with arithmetic mean (UPGMA). We also utilized a genotype selection index. We observed significant phenotypic variability within the population. Heritability coefficients ranged from 0.16 to 0.44 for the analyzed traits, with environmental variance exceeding genotypic variance. A strong negative correlation (-0.80) was found between pulp yield and fruit diameter. The results suggest the need for conservation and genetic improvement of the species. Additionally, we suggest the selection of key genotypes to boost the Amazonian bioeconomy, such as higher pulp yield, resulting in positive impacts on a regional or local scale, with greater income and social well-being.